Literature Review: The Relationship Of Upper Respiratory Tract Infections With Acute Otitis Media In Children - Maghfirah Tara Zakiyyah; Andi Tenri Sanna Arifuddin; Amira Trini Raihanah (Sean Institute, 2024)
Upper Respiratory Tract Infection is a common infection that occurs in the upper respiratory tract including the nose, paranasal sinuses, middle ear, pharynx, larynx and proximal part of the trachea. Upper Respiratory Tract Infection is one of the most frequent risk factors for the occurrence of Acute Otitis Media (AOM) in children due to anatomical factors, where in the middle ear development phase at childhood, the eustachian tube does have a horizontal position with minimal drainage compared to older age. This research method was carried out using a literature review by collecting various research journals and obtaining 5 samples of related research literature. This study concludes that there is a relationship between acute respiratory tract infections and acute otitis media in children. .